Food Security in Africa: Market and Trade Policy for Staple Foods in Eastern and Southern Africa - Minot, Nicholas (Oxford University Press, 2011)
This book includes a set of 12 studies of staple food markets in eastern and southern Africa, along with introductory and synthesis chapters. Chapters 2-8 are revised versions of papers presented at a workshop organised by the Food and Agriculture Organisation in Rome, while Chapters 9-13 are case studies commissioned after the workshop. Together, they present a rich, though not entirely consistent, picture of staple food production, marketing and policies in the region.